Analisis Kesulitan Belajar Siswa Pada Materi Tajhiz Mayit Kelas XII di SMAN 3 Lasalimu - Resna Yanti; Darmayanti Darmayanti; Abdul Rahim (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2026)
Learning difficulties of students are obstacles experienced by students during the learning process. This study aims to analyze students’ learning difficulties in tajhiz mayit material among twelfth-grade students at SMAN 3 Lasalimu, Buton Regency. Tajhiz mayit is an important component of Islamic Religious Education as it relates to fardhu kifayah, which must be understood and practiced by Muslims both theoretically and practically. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of Islamic Religious Education teachers and twelfth-grade students at SMAN 3 Lasalimu. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data condensation, data display, and conclusion drawing. The results show that students experience learning difficulties in understanding tajhiz mayit concepts, memorizing recitations and prayers of the funeral prayer, and mastering the correct procedures for managing a corpse, including washing, shrouding, praying for, and burying the deceased. These difficulties are caused by internal factors such as low learning motivation and interest, as well as external factors including less varied teaching methods, limited practical activities, inadequate learning facilities, and an unconducive learning environment. This study concludes that improving learning quality through varied instructional methods, contextual learning, practical activities, and continuous guidance and motivation is necessary to enhance students’ understanding of tajhiz mayit material.